2004
DOI: 10.1007/s10384-003-0046-7
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia Keratitis in a Human Immunodeficiency Virus Patient

Abstract: The treatment result for Nocardia keratitis in a human immunodeficiency virus patient was favorable after intensive use of 10% sulfacetamide eyedrops. Nocardia keratitis should be kept in mind as a possible causative organism when antifungal therapy fails in a keratitis case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…From the results of disc diffusion method, this species was sensitive to a relatively large number antibiotics compared with previous reports [1,2,[7][8][9]. Although the susceptibility to antibiotics in vitro may not always be reliable for in vivo sensitivity, the response to antibiotics was good in our patient.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…From the results of disc diffusion method, this species was sensitive to a relatively large number antibiotics compared with previous reports [1,2,[7][8][9]. Although the susceptibility to antibiotics in vitro may not always be reliable for in vivo sensitivity, the response to antibiotics was good in our patient.…”
Section: Discussioncontrasting
confidence: 61%
“…Although the susceptibility to antibiotics in vitro may not always be reliable for in vivo sensitivity, the response to antibiotics was good in our patient. In previous reports, 10% or higher concentration of sulfacetamide eyedrops was used [1,8], but in our case, we used 4% sodium sulfisoxazole solution with other antibiotics, which were effective.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…1 It has been reported that choroidal neovascularization (CNV) only infrequently accompanies dominant drusen, but when it does, it can lead to severe visual impairment. 2, 3 We report a Japanese patient with dominant drusen accompanied by CNV, which was successfully treated with photocoagulation.…”
Section: Case Of Dominantly Inherited Drusen Accompanied By Choroidalmentioning
confidence: 99%
“…However, the natural defense is a combination of innate immunity and specific acquired immunity. 1 Acquired immunodeficiency syndrome (AIDS) is caused by infection with the human immunodeficiency virus (HIV). This retrovirus infects and destroys T-helper cells, resulting in a profound deficiency of natural immunity.…”
Section: Ocular Bacterial Flora In Hiv-positive Patients and Their Sementioning
confidence: 99%